A project manager's book of tools and techniques : a companion to the PMBOK Guide - Dionisio, Cynthia Snyder, 1962- (Wiley, 2018)
"This valuable companion to the Project Management Institute'sA Guide to the Project Management Body of Knowledge (PMBOK Guide) ; Sixth Edition presents comprehensive examples and explanations of the tools and techniques presented in thePMBOK Guide. Designed specifically to assist both new and experienced project managers in handling all aspects of a project, this title explins the how ; when it comes to project management theory. Concrete examples of tools for project managers will fill the gap in this PM knowledge area and provide necessary guidance for both practicing project managers and students"-- Provided by publisher.
Includes index.
Machine generated contents note: Acknowledgments Introduction Part 1 Data Gathering 1.0 Data Gathering Techniques 1.1 Benchmarking 1.2 Brainstorming 1.3 Checksheets 1.4 Checklists 1.5 Focus Groups 1.6 Statistical Sampling Part 2 Data Analysis 2.0 Data Analysis Techniques 2.1 Alternative Analysis 2.2 Cost Benefit Analysis 2.3 Cost of Quality 2.4 Decision Tree 2.5 Earned Value Analysis 2.6 Influence Diagrams 2.7 Make or Buy Analysis 2.8 Performance Indexes 2.9 Regression Analysis 2.10 Reserve Analysis 2.11 Root Cause Analysis 2.12 Sensitivity Analysis 2.13 Stakeholder Analysis 2.14 SWOT Analysis 2.15 Technical Performance Analysis 2.16 Variance Analysis 2.17 What if Analysis Part Three Data Representation 3.0 Data Representation Techniques 3.1 Cause and Effect 3.2 Control Charts 3.3 Flow Charts 3.4 Histograms 3.5 Logical Data Model 3.6 Mind Mapping 3.7 P x I Matrix 3.8 Resource Breakdown Structure 3.9 Responsibility Assignment Matrix 3.10 Scatter Diagrams 3.11 Stakeholder Mapping Part Four Estimating 4.0 Estimating Techniques 4.1 Analogous Estimating 4.2 Bottom Up Estimating 4.3 Estimate at Completion 4.4 Estimate to Complete 4.5 Parametric Estimating 4.6 To Complete Performance Index 4.7 Three Point Estimating 4.8 Variance at Completion Part Five Interpersonal and Team Skills 5.0 Interpersonal and Team Skills 5.1 Conflict Management 5.2 Decision Making 5.3 Nominal Group Technique 5.4 Problem Solving Part Six Other 6.0 Other 6.1 Context Diagram 6.2 Critical Path Method 6.3 Funding Limit Reconciliation 6.4 Inspection 6.5 Leads and Lags 6.6 Precedence Diagramming Method 6.7 Prompt Lists 6.8 Prototypes 6.9 Resource Optimization 6.10 Rolling Wave Planning 6.11 Schedule Compression Index.
Keywords: Project management.; elektronické knihy; electronic books